ISOLASI DAN UJI ANTAGONIS MIKROORGANISME LOKAL (MOL) REBUNG BAMBU TERHADAP CENDAWAN Fusarium sp - Hilwa Walida; Fitra Syawal Harahap; Badrul Ainy Dalimunthe (UNIVERSITAS LABUHANBATU, 2020)
Efforts to increase the production of chilli plants are still experiencing obstacles. One of the diseases caused by fungi is fusarium wilt disease caused by Fusarium sp. The existence of this fungus attack makes one of the limiting factors that cause a decrease in red chili production. Local microorganism (MOL) solution is a fermented solution made from various local available resources. MOL solution contains micro and macro nutrients and also contains bacteria that have the potential to remodel organic matter, stimulate growth, and as a controlling agent for pests and plant diseases, so that MOL can be used both as a decomposer, biological fertilizer and as an organic pesticide, especially as a fungicide.In this research, bacterial isolation from MOL bamboo shoots will be carried out and then tested the isolates on Fusarium sp. The data of this research were analyzed descriptive. The results of isolation from bamboo shoot MOL which has been fermented for use as POC, obtained 8 bacterial isolates with different macroscopic and microscopic characteristics. All obtained bacterial isolates have the potential to inhibit the growth of fusarium fungal colonies. The most potential bacterial isolate was M6 isolate with a diameter of a pathogenic fungal colony that grew only by 2.1 cm. Keywords: Fusarium sp., Local Microorganisms, Bamboo Shoots